Metabolic Syndrome and Cardiovascular Risk Factors in a Fishing Community in Southern Italy - Angela Stufano; Simona D'Amore; Valentina Schino; Paolo Danza; Ivo Iavicoli; Piero Lovreglio (Elsevier, 2024)
Background: Work organization and psychosocial factors influencing sleep patterns may be significant risk factors for developing obesity and metabolic syndrome (MetS). However, the impact on the health of working patterns in the fishing sector is not well characterized. The aim of the study is to determine the prevalence of MetS and its components in fishermen and to analyze occupational-specific risk factors contributing to metabolic alterations. Methods: One hundred forty-three male fishermen from Apulia (Southern Italy) and 93 male university workers age-matched and from the same geographical area were included in this cross-sectional study. A questionnaire was administered to investigate socio-demographic variables, work activity, health status, and dietary habits. All subjects underwent clinical evaluation and blood sampling to depict their metabolic profile. Results: A higher body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (p < 0.001) were observed in fishermen than in university workers. No significant difference between the two groups was observed in the prevalence of MetS (15.4% fishermen vs 16.1% university workers) and its relevant diagnostic criteria, except abdominal obesity (42.7% fishermen vs 29.0% university workers, p = 0.021). The Castelli risk index, the monocyte/c-HDL ratio, and the Sokolow index were significantly greater in fishermen (p < 0.001). In the fishermen group, the total number of sleeping hours on working days was negatively correlated with WC (r = -0.17; p = 0.04), low-density lipoprotein cholesterol (c-LDL) (r = -0.21; p = 0.02), and the homeostasis model assessment (HOMA) index (r = -0.19; p = 0.02). Conclusion: The higher prevalence of obesity and the imbalance of the metabolic profile observed in fishermen could be related to occupational factors, including the specific working pattern that influences their sleeping hours and sleeping-waking rhythms.